2020
DOI: 10.3892/ol.2020.11430
|View full text |Cite
|
Sign up to set email alerts
|

High expression of FOXO3 is associated with poor prognosis in patients with hepatocellular carcinoma

Abstract: the role of forkhead box O3 (FOXO3) as a tumor suppressor gene and its association with the human lifespan is well documented. However, several studies have indicated that high expression of FOXO3 is also significantly associated with tumorigenesis. the aim of the present study was to determine the clinical significance of FOXO3 in the development and prognosis of hepatocellular carcinoma (Hcc). mrnA expression data of FOXO3 from the cancer genome Atlas database was analyzed through the UAlcAn online tool to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…Additionally, Lallemand et al (32) demonstrated that overexpression of FOXO6 activated breast cancer cell proliferation and inhibited the endogenous expression of FOXO6 to induce accumulation of cells in the G 0 / G 1 phase but did not cause apoptosis. Moreover, FOXO3 promotes cell proliferation and inhibits apoptosis in HCC cells, suggesting an association with poor prognosis (20,33). Furthermore, the upregulation of miR-421 expression elicits carcinogenic effects in nasopharyngeal carcinoma by inhibiting FOXO4 expression, resulting in the inhibition of cell proliferation and resistance to apoptosis (34).…”
Section: Roles Of Foxo Proteins In Cancer Cell Proliferationmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, Lallemand et al (32) demonstrated that overexpression of FOXO6 activated breast cancer cell proliferation and inhibited the endogenous expression of FOXO6 to induce accumulation of cells in the G 0 / G 1 phase but did not cause apoptosis. Moreover, FOXO3 promotes cell proliferation and inhibits apoptosis in HCC cells, suggesting an association with poor prognosis (20,33). Furthermore, the upregulation of miR-421 expression elicits carcinogenic effects in nasopharyngeal carcinoma by inhibiting FOXO4 expression, resulting in the inhibition of cell proliferation and resistance to apoptosis (34).…”
Section: Roles Of Foxo Proteins In Cancer Cell Proliferationmentioning
confidence: 99%
“…Lu et al (112) reported that FOXO3 was significantly activated in pathological specimens from patients with HCC. In addition, FOXO3 activated positive feedback pathways, such as the PI3K/AKT and mTOR complex 2 signaling pathways, in the hepatocytes from a transgenic mouse model with high FOXO3 expression, thereby promoting oxidative stress and DNA damage to regulate ROS (20). Alternatively, FOXO3 can activate the pentose phosphate pathway to form ROS-eliminating systems.…”
Section: Foxo3 In Hccmentioning
confidence: 99%
See 3 more Smart Citations